The effects of procedural justice on civil disobedience: evidence from protesters in three cities - Snipes, Jeffrey B. (Journal of crime and justice, 2019)
A large body of research reveals that procedural justice influences compliance with the law and legal authorities in a variety of settings. Recent research in protest settings has found that procedural justice influences protesters’ attitudes toward the use of violence against police as well as their self-reported violent behaviors toward police. Protesters who perceive the police as unjust are more willing to use or support the use of violence against the police. What is not yet known is the extent to which procedural justice might influence non-violent forms of illegal behavior among protesters. Based on data from surveys of protesters in three U.S. cities (Oakland, CA, New York, NY, and Washington, D.C.), we examine the linkages between procedural justice and civil disobedience.